Challenges and Solutions in the Implementation of Technology-Based Learning Models - Febiola, Desi; Annisa, Nurul; Artika , Reni; Andikos , Adi Fitra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research delves into the multifaceted challenges posed by the digital divide in the adoption and implementation of technology-based learning models, particularly in remote and underserved areas. Drawing on surveys and in-depth interviews with both teachers and students, the study reveals that the primary obstacles to effective technology integration in education are limited access to reliable internet connectivity and the scarcity of technological devices such as computers or tablets. These barriers not only hinder the daily learning experience but also exacerbate educational inequalities, particularly in rural or economically disadvantaged regions. To address these challenges, the research proposes a range of solutions aimed at improving access to technology and enhancing its pedagogical effectiveness. These include the adoption of low-cost or simpler technological tools that can function in environments with limited infrastructure, the creation of offline learning resources that do not rely on constant internet access, and the provision of targeted teacher training to help educators make the best use of the technology available to them. The study underscores the importance of a holistic approach to bridging the digital divide—one that takes into account local contexts, infrastructure limitations, and the need for professional development in order to create more inclusive and equitable educational opportunities for all students, regardless of their geographical location.